2021
DOI: 10.1111/jcmm.16450
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitizing effects of curcumin alone or combined with GLUT1 siRNA on laryngeal carcinoma cells through AMPK pathway‐induced autophagy

Abstract: In this study, we investigated the ability of curcumin alone or in combination with GLUT1 siRNA to radiosensitize laryngeal carcinoma (LC) through the induction of autophagy. Protein levels in tumour tissues and LC cells were measured by immunohistochemistry and Western blotting. In vitro, cell proliferation, colony formation assays, cell death and autophagy were detected. A nude mouse xenograft model was established through the injection of Tu212 cells. We found that GLUT1 was highly expressed and negatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
(67 reference statements)
1
7
0
Order By: Relevance
“…As reported by some previous studies [20,21], there is also high expression of GLUT-1 in laryngocarcinoma, and the expression of GLUT-1 is related to the radioresistance of laryngocarcinoma. Thus, inhibiting the expression of GLUT-1 can improve the radiosensitivity of laryngocarcinoma.…”
Section: Introductionsupporting
confidence: 69%
“…As reported by some previous studies [20,21], there is also high expression of GLUT-1 in laryngocarcinoma, and the expression of GLUT-1 is related to the radioresistance of laryngocarcinoma. Thus, inhibiting the expression of GLUT-1 can improve the radiosensitivity of laryngocarcinoma.…”
Section: Introductionsupporting
confidence: 69%
“…Hypoxia induces the stabilization of HIF‐1α, which is associated with radiotherapy resistance in head and neck carcinoma 31 . Our previous research indicated a significant association between Glut‐1 and radioresistance in laryngeal carcinoma 20‐22,32,33 . Furthermore, HIF‐1α and Glut‐1 double knockout using the CRISPR/CAS9 system showed synergistic regulation of biological behaviour in laryngeal carcinoma cells 23 .…”
Section: Discussionmentioning
confidence: 94%
“…31 Our previous research indicated a significant association between Glut-1 and radioresistance in laryngeal carcinoma. [20][21][22]32,33 Furthermore, HIF-1α and Glut-1 double knockout using the CRISPR/CAS9 system showed synergistic regulation of biological behaviour in laryngeal carcinoma cells. 23 Glut-1 antisense oligodeoxynucleotides facilitated the response to radiotherapy in laryngeal carcinoma tissue via autophagy regulation.…”
Section: Discussionmentioning
confidence: 98%
“…It might function as a novel anticancer drug to assist chemoradiotherapy by inhibiting a site overlapping the cytochalasin B of GLUT1 and metabolism-related enzymes (129)(130)(131). In some studies concerning cervical cancer, the theory that curcumin enhances radiosensitivity by inhibiting GLUT1-induced PI3K/AKT/mTOR pathway or MAPK/mTOR/ ULK1 pathway and subsequently activating autophagy has also been confirmed (121,125,132). Therefore, we speculate that there may be a similar mechanism in EC.…”
Section: Glucose Transporter-related Radiotherapy Sensitivitymentioning
confidence: 99%
“…A large amount of data indicate that the anti-radiosensitivity in EC refers to PI3K/PTEN/AKT/mTOR signaling pathway, MAPK signaling pathway, and NF-kB signaling pathway; each of them is directly or indirectly involved in tumor radioresistance and GLUT1-induced malignant processes that include proliferation, angiogenesis, and EMT in EC (124,125). It is clear that either upstream elements' inhibitors of these significant pathways or inhibitors of GLUT1 itself should play a therapeutic role in the radio-resistance of EC.…”
Section: Glucose Transporter-related Radiotherapy Sensitivitymentioning
confidence: 99%